The transmission of companies in crisis to their workers through social economy formulas. Socially responsible restructures before the declaration of bankruptcy - Carlos Vargas Vasserot (AECOOP Escuela de Estudios Cooperativos, 2018)
Associated work cooperatives and labour companies, as social economy enterprises, seem prima facie formulas especially suitable for the continuation of a company in crisis by workers. This paper exposes the barriers, essentially legal, that exist for the transmission of companies in prebankruptcy crisis to their own workers. After an analysis of the solutions offered in these cases by some of legal systems of our environment, it will be highlighted the lack of incentives that exist in ours to facilitate this type of socially sustainable restructuring, making some lege ferenda proposals. Finally, it will be analyzed, in some detail, the two main ways to transfer companies to workers in these cases: the previous owner transmit the company or a productive unit to the cooperative or to the labour company constituted by the workers; or the transmission of the commercial company to its employees through a sale of shares or social participations, which can then be transformed into a social economy company.